‘OVERLOAD’ POTRET TRANSPORTASI ANGKUTAN BARANG DALAM KARYA STREET PHOTOGRAPHY - sulistiyo wibowo (Politeknik Negeri Media Kreatif, 2021)
Humans are creatures that are able to move and move from one place to another. Long before the wheel was discovered as part of the means of human transportation, animals and livestock such as horses, cows, camels and even elephants were used as a means of transportation. Apart from being a tool to speed up and lighten the travel time of these animals, sometimes the burden is attached to the rider. After the wheels were found, humans made transport vehicles that functioned as places for passengers and goods which were then pulled by animals so that the loads carried became more efficient and more efficient. Along with the development of time from time to time until finally motorized vehicles were found, the distance between the movement of people and goods was getting farther, more numerous and faster. Humans can move freely with current road facilities and adequate facilities. Almost everyone today can afford a vehicle from a bicycle to a plane depending on the abilities and needs of each individual. Movement or mobilization is not only human but also goods. Movable goods clearly require transportation assistance and humans as the perpetrators and are supported by the ease of road facilities and infrastructure. Each vehicle created has its own specifications and specifications, be it designation, capacity and recommended load. For example, passenger vehicles are not allowed to carry goods and vice versa. Especially if it is related to the recommended load capacity, whether it is a passenger vehicle or goods, it will clearly affect the safety of both the driver, passengers and luggage. Seeing the tendency in Indonesia, things related to the transportation function and discipline are often violated, the writer and photographer in this study is interested in the theme of 'overload', namely the portrait of transportation, especially freight transport in Indonesia, which is often seen carrying excess burden or over capacity in street / Street photography works. Photography Keywords: Street Photography, Transportation, Street Photography